2019
DOI: 10.24832/wln.v17i1.365
|View full text |Cite
|
Sign up to set email alerts
|

Mistifikasi Ritual Sistem Pertanian Tradisional Masyarakat Ajatappareng, Sulawesi Selatan

Abstract: The Ajatappareng region is known as the most important rice producer in South Sulawesi. Historical sources and archaeological evidence show that agricultural tradition in this region has been going on for at least the 14th century. In that time span, the Ajatappareng community carried out an agricultural system as a system of knowledge passed down from generation to generation. This study aims to obtain a record of knowledge related to the traditional farming system of the Ajatappareng community. It used etnog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
1
0
2
Order By: Relevance
“…Yang berarti pula hidup manusia tidak terancam. Pengharapan akan hasil panen yang baik juga sangat bergantung pada kepatutan masyarakat petani pada petuah-petuah dan aturan-aturan yang sudah dijalankan secara turun-temurun (Somba et al, 2019).…”
Section: Fungsi Spiritual Ritual Hole Dalam Pertanian 1 Tercapainya K...unclassified
“…Yang berarti pula hidup manusia tidak terancam. Pengharapan akan hasil panen yang baik juga sangat bergantung pada kepatutan masyarakat petani pada petuah-petuah dan aturan-aturan yang sudah dijalankan secara turun-temurun (Somba et al, 2019).…”
Section: Fungsi Spiritual Ritual Hole Dalam Pertanian 1 Tercapainya K...unclassified
“…Perubahan fungsi dan makna juga terjadi pada temuan lumpang batu yang berada di Situs Watugong, melihat konteks ruang dari temuannya yang umumnya merupakan daerah persawahan sehingga dapat disimpulkan bahwa lumpang batu berfungsi sebagai sarana pertanian untuk menumbuk padi atau biji-bijian dalam fungsi profannya (Somba, 2002). Fungsi sakral dari lumpang batu menyangkut kepada pemujaan arwah leluhur yang dimaksudkan agar kekuatan magis dari leluhur dapat memberikan keberhasilan dalam upaya bercocok tanam (Jati dan Wahyudi, 2015: 122-123).…”
Section: Fungsi Dan Makna Tinggalanunclassified
“…The economic and ecological impacts of modernization for rural communities who still adhere to traditional wisdom can be resolved by holding rituals as a form of shielding from harm and can resist reinforcements. (Somba et al, 2019) (Setiawan, 2020) (Yashi, 2018). Various studies have shown that local wisdom related to agriculture, food and fertility is actualized in rituals (Dewi et al, 2018) (Ursula, 2015).…”
Section: Maintaining Harmony Through Ritualsmentioning
confidence: 99%